The role of social capital in the formation of a sustainable community - Egorova, Maria; Garanina, Olga; Petrova, Svetlana; Okhrimenko, Igor (Opción, 2019)
The purpose of our research is to identify the problems in the field of social capital based on a survey of students and suggest possible solutions to them. To achieve this goal, we conducted an empirical study, in which the main method of obtaining information was a survey that involved undergraduate students of Russian state universities. As a result, students may not fully understand the definition of social capital, but they realize that it affects community development. In conclusion, the higher the level of social capital and social networks, the better and more stable this development will be.